Upaya Penurunan Tingkat Kanibalisme Udang Windu (Penaeus monodon) dengan Penambahan Dosis Suplemasi TriptofanYang Berbeda - Suharyanto Suharyanto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
The aim of this experiment was to find out the suitable dosage of tryptophan  mixed  in diet of  trash fish were fed and to decrease canibalism levels of tiger prawn (Penaeus monodon) reared in  the aquarium. The research was conducted in research station of Research Institute for Brackishwater Aquaculture Maranak, Maros South Sulawesi for 28 days.Twelve aquaria were used of this research and the dimention of 60 x 40 x 40 cm.  Tiger prawn seed of post larva of 35th from hatchery were used to this research and the dimention of 1,4 ± 0.1 cm body length and 0,01 ± 0.01 g body weight.  Twentyfive pieces of tiger prawn seed were spreaded on the each aquaria. The treatments were applied of dosage of tryptophan were mixed in the trash fish  (Sardinella sp) as much as  (A): 0 % of  biomass total, (B): 0,5 %, (C): 1,0 % and (D): 1,5 % of  biomass total with three replicates respectively. Variables monitored growth of body weigth, canibalism levels, survival rate of twentyfive tiger prawn seed and water quality. Experimental design used complate randomized design. During of rearing were fed trash fish with frequency of twice a days of dosage 15 % of total body weight. The result showed that the   tiger prawn seed fed the diet with additional 0,5 - 1,5 % tryptophan had significantly lower (P<0.05) cannibalisms compared to the tiger prawn seed feed the control diet.  The tiger prawn seed fed the diet with additional 1,5 % tryptophan had significantly higher (P<0.05) survival rate compared to the crablet fed the control diet.  However, there were not significantly different specific growth rate among the treaments.  Based on this result that additional 0,5 - 1,5 % tryptophan could be decrease cannibalisms of tiger prawn seed during experiment.